Purification, crystallization and preliminary X-ray diffraction analysis of carboxyhaemoglobin-II from the fish Piaractus mesopotamicus (pacu) - Fadel, V; Honda, R. T.; Dellamano, M.; Smarra, ALS; Delatorre, P.; Olivieri, JR; Bonilla-Rodriguez, G. O.; de Azevedo, W. F. (Munksgaard Int Publ Ltd, 2000)
Carboxyhaemoglobin-II isolated from the pacu (Piaractus mesopotamicus) has been crystallized and X-ray diffraction data were collected to 2.0 Angstrom resolution using synchrotron radiation. Crystals were characterized as belonging to the space group I23; preliminary structural analysis reveals the presence of one dimer in the asymmetric unit.